Level of employers awareness towards the importance of employee benefits among Anika Insurance Brokers clients / Nur Zafira Kamardin - Kamardin, Nur Zafira (Faculty of Business and Management, 2011)
This research has been conducted meeting point on employer awareness towards employee benefits scheme. An employee benefit is any kind of benefits provided to employees in addition to their normal wages or salaries. Anika Insurance Brokers plays an important role as an intermediary between insurance companies and employers in order to ensure employees or workers have their benefits as well as their welfare at the event of any accidents that related to their employment which may affect the public financial security. Employees in Malaysia are entitled to participate in various schemes which provide for social insurance and retirement benefits. This scheme provides retirement benefits for members through the management of their savings in an efficient and reliable manner. These savings are accrued for each employee through contributions from employees and their employers. In view of the current demand for skilled workers, attractive incentives are currently being offered to Malaysian citizens working and residing overseas to encourage their return to Malaysia. The purpose of these research are mainly focus on employers awareness on employee benefits scheme among Anika Insurance brokers clients and also the factors that influenced their awareness. This study is done by using secondary data and distribution of questionnaires to clients of Anika Insurance Brokers to find the issue. From the findings obtained, there are some factors that contribute to the employer awareness on employee benefits scheme. Thus, by conducting this study the researcher hope that the result and some of recommendations can improve the awareness level of employers towards employee benefits scheme.